إتجاهات أساتذة التاعليم المتوسط نحو ممارسة النشاط الرياضي الترويحي وفقا لبعض النتغيرات ( السن- التخصص الأكاديمي ) - بوخلوة, بشير (Institut d'Éducation Physique et Sportive - Mostaganem 2023/2024, 2024)
هدفت دراستنا هذه إلى معرفة مستوى إتجاهات أساتذة التعليم المتوسط نحو ممارسة الأنشطة الرياضية الترويحية وكشف الفروق بينهم وفقا لمتغيرات السن والتخصص الأكاديمي وسنوات الخبرة، وإلى إعطاء نظرة إيجابية لممارسة النشاط الرياضي الترويحي في الحياة اليومية، ولأجل ذلك أجريت الدراسة على عينة قدرت بمائة (100) أستاذ (ذكور وإناث) من أساتذة التعليم المتوسط لثمانية (8) متوسطات بولاية معسكر موزعين كالآتي 2 لبلدية معسكر و3 لبلدية تغنيف 2 لبلدية واد الأبطال و1 لبلدية السهايلية، وقد تم إستخدام المنهج الوصفي المسحي لذلك، ولجمع البيانات تم إسخدام مقياس الإتجاهات النفسية نحو ممارسة النشاط الرياضي الترويحي لمحمد عبد المنعم، ولتحليل البيانات إستعمل الباحث حزمة البرامج الإحصائية SPSS. والإستنتاجات التي توصلنا إليها كما يلي: ـ مستوى إتجاهات أساتذة التعليم المتوسط نحو ممارسة النشاط الرياضي الترويحي مرتفع. ـ لا توجد فروق ذات دلالة إحصائية في قياس الإتجاهات نحو النشاط الرياضي الترويحي لدى أفراد العينة بالنسبة لمتغير السن وسنوات الخبرة. ـ توجد فروق ذات دلالة إحصائية في قياس الإتجاهات نحو النشاط الرياضي الترويحي لدى عينة البحث بالنسبة لمتغير التخصص الأكاديمي. وأهم الإقتراحات نذكر مايلي: الإهتمام بصحة الأساتذة النفسية والبدنية وتشجيع ممارسة الأنشطة الرياضية الترويحية بنشر التوعية والثقافة عن طريق وسائل الإعلام المتنوعة وعقد الندوات لإظهار أهميتها البالغة ودورها الإيجابي في الحياة اليومية، وتوفير أهم الوسائل والمنشآت لذلك، مع توسيع البحوث والدراسات في هذا المجال. // // // // Summary of the study: Our study aimed to know the level of middle school teachers’ attitudes towards practicing recreational sports activities and to reveal the differences between them according to the variables of age, academic specialization and years of experience, and to give a positive view of practicing recreational sports activities in daily life. For this purpose, the study was conducted on a sample estimated at one hundred (100) teachers. (Males and females) of middle school teachers for eight (8) middle schools in the state of Mascara, distributed as follows: 2 for the municipality of Mascara, 3 for the municipality of Tighenif, 2 for the municipality of Oued El Abtal, and 1 for the municipality of Al-Sahailia. The descriptive survey method was used for this, and to collect data, a measure of psychological attitudes towards practicing sports activity was used recreational by Mohamed Abdel Moneim. To analyze the data, the researcher used the statistical software package SPSS. The conclusions we reached are as follows: The level of middle school teachers attitudes towards practicing recreational sports activity is high. There are no statistically significant differences in measuring attitudes toward recreational sports activity among sample members with respect to the variables of age and years of experience. There are statistically significant differences in measuring attitudes towards recreational sports activity among the research sample in relation to the academic specialization variable. The most important suggestions are the following: paying attention to the mental and physical health of teachers and encouraging the practice of recreational sports activities by spreading awareness and culture through various media outlets and holding seminars to show their great importance and positive role in daily life, and providing the most important means and facilities for that, and finally, increasing research and studies in the field of sports recreation.
MEPS-2024-14
Keywords: الإتجاهات ـــ الترويح والنشاط الرياضي الترويحي // // Trends- Recreation and Recreational sports activity